Spinning-induced in-situ synthesized strong-carbon-absorption compact MOF nano-fiber membrane as well as preparation method and application thereof

The dense MOF nanofiber film loaded with bimetallic MOFs nanocrystals was prepared by spin-induced in situ synthesis technology, and through amino modification, the mechanical strength and structural stability of traditional MOFs powder materials in industrial applications were solved, achieving efficient CO2 adsorption and separation effects.

CN120211111APending Publication Date: 2025-06-27CHINA UNIV OF MINING & TECH
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510434431.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-08
Publication Date
2025-06-27

AI Technical Summary

Technical Problem

Traditional MOFs powder materials have problems such as insufficient mechanical strength, structural collapse, drastic increase in bed pressure drop and dust entrainment in industrial applications, which are difficult to meet the engineering needs under complex working conditions such as industrial terminal waste gas.

Method used

Through spin-induced in situ synthesis technology, a dense MOF nanofiber film supported by bimetallic MOFs nanocrystals was prepared, and its adsorption performance was enhanced by amino modification.

Benefits of technology

Nanofiber film materials with high specific surface area, dense MOFization, structural stability and performance durability have been achieved, which significantly improves CO2 adsorption capacity and separation selectivity, and are suitable for carbon capture and separation of industrial terminal waste gases.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120211111A_ABST
    Figure CN120211111A_ABST
Patent Text Reader

Abstract

The invention provides a spinning-induced in-situ synthesized strong-carbon-absorption compact MOF nano-fiber membrane as well as a preparation method and application thereof. The method comprises the following steps: S1, co-dissolving polylactic acid, a zinc source and a cobalt source in a solvent A to prepare a bimetallic spinning precursor solution; s2, preparing a metal salt loaded nano-fiber membrane from the precursor solution obtained in the step S1 through a spinning process; s3, performing in-situ synthesis on the nano-fiber membrane obtained in the step S2 in a ligand solution composed of an organic ligand and a solvent B to prepare a compact MOF nano-fiber membrane; and S4, carrying out amination modification on the dense MOF nano-fiber membrane obtained in the step S3 in a mixed solution composed of a silane reagent and a solvent C to prepare the strong-carbon-absorption dense MOF nano-fiber membrane. The nano-fiber membrane prepared by the invention not only has the remarkable characteristics of bimetallic and Lewis alkaline adsorption sites, compact MOF, core-shell morphology, hierarchical pore structure and the like, has high carbon dioxide adsorption capacity and excellent separation selectivity, and is an efficient industrial terminal waste gas carbon capture and separation membrane material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of gas screening membranes for carbon capture and selective adsorption separation of industrial terminal exhaust gas, and particularly relates to a spinning-induced in-situ synthesis of a strong carbon-absorbing dense MOF-based nanofiber membrane, a preparation method thereof, and an application thereof. Background Art

[0002] The excessive accumulation of carbon dioxide (CO2) caused by industrial terminal exhaust gas emissions has posed a global environmental challenge. According to the IPCC's Sixth Assessment Report, the atmospheric CO2 concentration has soared from 280 ppm before the Industrial Revolution to 420 ppm, and its greenhouse effect contribution rate exceeds 65%. Developing efficient carbon capture and storage (CCUS) technologies has become a key path to achieving the carbon neutrality goal. The current mainstream technology system includes chemical absorption, cryogenic distillation, solid adsorption, and membrane separation. Among them, the solid physical adsorption technology has attracted much attention due to its advantages such as low energy consumption and compact equipment. However, traditional adsorbents such as 13X zeolite, activated carbon, and MCM-41 mesoporous silica generally have the "trade-off" effect of mutual restriction between adsorption capacity and selectivity. This problem has promoted the research and development transformation of new adsorbing materials - an ideal material needs to have a high specific surface area, precise pore size regulation, a matching gas kinetic diameter, and specific adsorption sites (such as open metal sites, amino functional groups) to achieve efficient capture and high-selectivity separation of low-concentration CO2.

[0003] As a third-generation porous adsorbing material, metal-organic frameworks (MOFs) have shown unique advantages in the field of gas adsorption separation with their ultra-high specific surface area, adjustable pore size, and surface chemical modifiability. The nanoscale pores formed by the periodically arranged metal nodes and organic ligands generate strong adsorption sites through open metal sites and functionalized ligands, significantly improving the CO2 adsorption capacity and CO2 / N2 separation selectivity. Experimental studies have shown that the CO2 adsorption capacities of some MOFs (such as Mg-MOF-74, SIFSIX-3-Ni) have exceeded those of traditional zeolites and activated carbons. However, the rigid crystal structure of MOFs results in insufficient mechanical strength, and the structure is prone to collapse during the dynamic adsorption process. Moreover, powder materials have problems such as a sharp increase in bed pressure drop and dust entrainment in fixed-bed applications. Therefore, there is an urgent need to seek to prepare MOFs into membrane materials to effectively alleviate the serious constraints in engineering under complex working conditions such as industrial terminal exhaust gas.

[0004] To break through the engineering bottlenecks of MOF powder materials in industrial applications, researchers are committed to developing structured MOF composite systems. The current mainstream technical routes include loading on flexible porous matrices (microbeads / membranes / aerogels), coating on the surface of porous ceramics, and in-situ crystallization composite of electrospun nanofibers. The Zhang team [Zhang Z.S., et al. Chem. Phys. Lett. 2022, 801 139703.] used the supercritical CO2-assisted impregnation method to construct a ZIF-8 / PI composite material (loading amount 10 wt%) on a polyimide aerogel matrix, and its CO2 adsorption capacity reached 0.72 mmol / g (298K / 1bar). In another study, Rezaei et al. [Rezaei F., et al. Chem. Eng. J. 2017, 313 1346–1353.] loaded UTSA-16(Co) crystals (loading amount 55 wt%) on the surface of cordierite honeycomb ceramics through an impregnation-pyrolysis process, achieving a CO2 adsorption performance of 1.1 mmol / g. However, the above physical loading methods generally have problems such as weak interfacial bonding and uneven dispersion of MOFs, resulting in a high loss rate of active components during cyclic use. Although the above composite materials have improved the adsorption capacity to a certain extent, due to the limited compatibility between the matrix and MOFs, the MOF loading amount is often low, and the stability and reusability of the MOF composite materials are affected due to MOF leakage or aggregation during use. In contrast, the strategy of in-situ growing MOFs on a support matrix such as electrospun nanofibers can effectively adjust the MOF loading amount and type, and increase the interfacial affinity between MOFs and the support substrate, which is important for improving CO2 adsorption performance while maintaining the structural stability and durability of MOF composite materials.

[0005] In addition to directly synthesizing MOFs, researchers have also enhanced the interaction between CO2 and MOFs through metal exchange, ligand functionalization, and mixed ligand strategies. Recently, the construction of multi-component MOFs using the mixed metal strategy (i.e., introducing two different metals into a single framework) has attracted extensive attention. This method can not only explore the differential roles of metals in the framework but also endow the material with new functions beyond single-metal MOFs. Charge transfer between heterogeneous metals can enhance the quadrupole interaction of CO2, and the synergistic effect of bimetallic sites significantly increases the adsorption enthalpy. Currently, the construction of mixed metal MOFs mostly relies on post-synthesis metal replacement methods, template-assisted construction methods, or solvothermal co-assembly methods to achieve the doping of the second metal. However, the one-step direct synthesis faces the problems of lattice mismatch and phase separation, and it is necessary to precisely control the coordination kinetics of metal precursors to enhance the stable framework and highly efficient carbon capture composite materials with chemical functionalization. The core challenge lies in simultaneously meeting the requirements of framework stability and CO2 adsorption function. Summary of the Invention

[0006] The object of the present invention is to prepare a spinning-induced in-situ synthesized strong carbon-absorbing dense MOF-functionalized nanofiber membrane to meet the requirements of carbon capture and selective adsorption separation for industrial end-of-pipe waste gas.

[0007] To achieve the above object, the present invention provides a spinning-induced in-situ synthesized strong carbon-absorbing dense MOF-functionalized nanofiber membrane, its preparation method and application. In the present invention, polylactic acid, a zinc source and a cobalt source are dissolved in solvent A to prepare a bimetallic spinning precursor solution; the obtained bimetallic spinning precursor solution is prepared into a metal salt-loaded nanofiber membrane by a spinning process; the obtained metal salt-loaded nanofiber membrane is in-situ synthesized in a ligand solution composed of an organic ligand and solvent B to prepare a dense MOF-functionalized nanofiber membrane; the dense MOF-functionalized nanofiber membrane is subjected to amination modification in a mixed solution composed of a silane reagent and solvent C to prepare a strong carbon-absorbing dense MOF-functionalized nanofiber membrane.

[0008] According to the first aspect of the present invention, a preparation method of a spinning-induced in-situ synthesized strong carbon-absorbing dense MOF-functionalized nanofiber membrane is provided, including the following steps: Step S1, preparing a bimetallic spinning precursor solution: dissolving polylactic acid, a zinc source and a cobalt source in solvent A to prepare a bimetallic spinning precursor solution; Step S2, preparing a metal salt-loaded nanofiber membrane: preparing a metal salt-loaded nanofiber membrane from the bimetallic spinning precursor solution obtained in Step S1 by a spinning process; Step S3, preparing a dense MOF-functionalized nanofiber membrane: in-situ synthesizing the metal salt-loaded nanofiber membrane obtained in Step S2 in a ligand solution composed of an organic ligand and solvent B to prepare a dense MOF-functionalized nanofiber membrane; Step S4, preparing a strong carbon-absorbing dense MOF-functionalized nanofiber membrane: subjecting the dense MOF-functionalized nanofiber membrane obtained in Step S3 to amination modification in a mixed solution composed of a silane reagent and solvent C to prepare a strong carbon-absorbing dense MOF-functionalized nanofiber membrane.

[0009] Preferably, in Step S1, the zinc source is one or more of zinc acetate dihydrate, zinc nitrate hexahydrate, zinc sulfate heptahydrate, zinc chloride, zinc perchlorate, zinc fluoride, zinc formate, zinc citrate, and the cobalt source is one or more of cobalt nitrate hexahydrate, cobalt acetate tetrahydrate, cobalt sulfate heptahydrate, cobalt chloride hexahydrate, cobalt carbonate, cobalt oxalate dihydrate, cobalt hydroxide, cobalt oxide, cobalt acetylacetonate, cobalt perchlorate hexahydrate; in Step S1, solvent A is one or more of dichloromethane, N,N-dimethylformamide, chloroform, methanol, ethanol, acetone, tetrahydrofuran, N,N-dimethylacetamide, hexafluoroisopropanol, dioxane, toluene, dimethyl sulfoxide.

[0010] Preferably, in Step S1, the mass fraction of polylactic acid in the bimetallic spinning precursor solution obtained in Step S1 is 5% to 25%, the mass ratio of polylactic acid to the zinc source is 10:1 to 1:10, and the mass ratio of polylactic acid to the cobalt source is 10:1 to 1:10.

[0011] Preferably, the spinning process in step S2 is one or more of high-voltage electrospinning, wet solution spinning, dry solution spinning, rotary centrifugal spinning, high-speed air jet spinning, microfluidic spinning, emulsion spinning, reaction spinning, gel spinning, and liquid crystal spinning. The thickness of the metal salt-loaded nanofiber membrane obtained in step S2 is 50-200 μm, and the diameter of the nanofibers is 200-900 nm.

[0012] Preferably, the spinning process in step S2 is the high-voltage electrospinning process, and the spinning parameters are set as follows: the working voltage is 5-50 kV, the receiving distance is 10-30 cm, the solution propulsion speed is 0.1-2 mL / h, the nozzle diameter is 0.1-1 mm, the collector rotation speed is 500-2000 rpm, the temperature is 20-60°C, and the humidity is 10%-80% RH.

[0013] Preferably, the spinning process in step S2 is the wet solution spinning process, and the spinning parameters are set as follows: the spinneret hole diameter is 0.1-0.5 mm, the spinneret pressure is 0.1-1 MPa, the injection speed is 1-10 mL / min, and the receiving distance is 10-30 cm.

[0014] Preferably, the spinning process in step S2 is the rotary centrifugal spinning process, and the spinning parameters are set as follows: the rotation speed is 5000–100000 rpm, the rotation radius is 1-10 cm, the spray hole diameter is 0.05-1 mm, the receiving distance is 10-50 cm, the solution flow rate is 0.1-10 mL / h, and the ambient temperature is 20-80°C.

[0015] Preferably, the spinning process in step S2 is the high-speed air jet spinning process, and the spinning parameters are set as follows: the air flow speed is 50-500 m / s, the spinneret hole diameter is 0.05-1 mm, the receiving distance is 10-100 cm, the solution flow rate is 0.1-20 mL / h, the ambient temperature is 20-120°C, and the ambient humidity is 10%-70% RH.

[0016] Preferably, the organic ligand in step S3 is one or more of 2-methylimidazole, 4-methylimidazole, 2-ethylimidazole, 2-aminoimidazole, 2-methylbenzimidazole, 1-vinylimidazole, 2-ethylbenzimidazole, 1-phenylimidazole, and 2-aminobenzimidazole, and the solvent B is one or more of water, methanol, ethanol, N,N-dimethylformamide, N,N-dimethylacetamide, toluene, chloroform, acetone, tetrahydrofuran, and ionic liquid.

[0017] Preferably, the mass ratio of the organic ligand in step S3 to the total of the zinc source and the cobalt source in the metal salt-loaded nanofiber membrane obtained in step S2 is 10:1-1:10, and the in-situ synthesis conditions are a temperature of 0-50°C and a time of 0.5-24 h.

[0018] Preferably, the silane reagent in step S4 is one or more of 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-aminopropylmethyldimethoxysilane, N-methyl-3-aminopropyltrimethoxysilane, 3-aminopropyltrimethoxysilane, and 4-aminophenyltrimethoxysilane; and the solvent C in step S4 is one or more of methanol, ethanol, N,N-dimethylformamide, N,N-dimethylacetamide, water, toluene, chloroform, dimethyl sulfoxide, and N-methyl-2-pyrrolidone.

[0019] Preferably, the mass ratio of the silane reagent in step S4 to the solvent C in step S4 to the dense MOF nanofiber membrane obtained in step S3 is 5-15:20-40:1, and the conditions for the amino modification in step S4 are temperature of 0-60°C and time of 1-48 h.

[0020] In order to achieve the above object, according to the second aspect of the present invention, the present invention also provides a strong carbon-absorbing dense MOF nanofiber membrane obtained by the above-mentioned preparation method, and the specific surface area of ​​the nanofiber membrane is 527 m 2 / g~681 m 2 / g, pore size is 0.69 nm~1.22 nm, and metal framework loading is 65~75 wt%.

[0021] In order to achieve the above-mentioned purpose, according to the third aspect of the present invention, the present invention also provides the application of the aforementioned carbon-absorbing dense MOF nanofiber membrane in carbon capture in industrial terminal exhaust gas, energy production process, transportation, agriculture and ecology, as well as biomedicine and semiconductor precision manufacturing industries.

[0022] Preferably, the CO2 adsorption capacity of the strongly carbon-absorbing and dense MOF nanofiber membrane is 3.6~4.7 mmol / g, the CO2 / N2 selectivity is 132~184, and the CO2 / CH4 selectivity is 32~61.

[0023] The beneficial effects of the present invention are as follows: (1) By performing amination and post-modification on the surface of the dense MOF-functionalized nanofiber membrane, dual metals and Lewis basic adsorption sites are introduced simultaneously, and the adsorption sites of the nanofiber membrane are precisely adjusted by acid-base interaction to enhance the CO2 affinity and sensitivity; (2) Uniformly anchor the dual-metal MOFs nanocrystals on the nanofibers with strong interfacial affinity to achieve dense MOF-functionalization, structural stability, and performance durability; (3) Convert the MOFs particles into a flexible, self-supporting nanofiber membrane with a hierarchical porous structure and a three-dimensional network woven shape, which helps to construct an efficient gas transport channel; (4) Through the optimization of the synthesis process, the prepared material not only has dual metals and Lewis basic adsorption sites, dense MOF-functionalization, core-shell morphology, and hierarchical pore structure, but also has significant advantages such as high carbon dioxide adsorption capacity and excellent separation selectivity. It is an efficient membrane material for carbon capture and separation of industrial end-of-pipe waste gas.

[0024] The technical solution proposed by the present invention enables a spinning-induced in-situ synthesis of a strong carbon-absorbing dense MOF-functionalized nanofiber membrane with abundant dual metals and Lewis basic adsorption sites, a high specific surface area (527 m 2 / g~681 m 2 / g), small pore size (0.69nm~1.22 nm), high carbon dioxide adsorption capacity (3.6~4.7 mmol / g), and excellent CO2 / N2 (132~184) and CO2 / CH4 (32~61) separation selectivity, dense MOF-functionalization (MOF loading of 65~75 wt%), etc. The design of this material aims to meet the technical field of gas screening membranes for carbon capture and selective adsorption separation of industrial end-of-pipe waste gas, and has broad application potential and market prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following will briefly introduce the drawings required for use in the embodiments or the description of the prior art. Obviously, the following drawings are only some embodiments of the present invention. For those of ordinary skill in the art, other drawings can be obtained based on these drawings without creative efforts.

[0026] Figure 1 It is a schematic diagram of the method flow of the present invention.

[0027] Figure 2 It is a scanning electron microscope image of the strong carbon-absorbing dense MOF-functionalized nanofiber membrane in Example 1.

[0028] Figure 3 It is a transmission electron microscope image of the strong carbon-absorbing dense MOF-functionalized nanofiber membrane in Example 1.

[0029] Figure 4It is the elemental mapping image of the strongly carbon-absorbing and dense MOF-functionalized nanofiber membrane in Example 1.

[0030] Figure 5 It is the Fourier transform infrared spectrum of the strongly carbon-absorbing and dense MOF-functionalized nanofiber membrane in Example 1.

[0031] Figure 6 It is the X-ray diffraction spectrum of the strongly carbon-absorbing and dense MOF-functionalized nanofiber membrane in Example 1.

[0032] Figure 7 It is the nitrogen adsorption-desorption isotherm curve of the strongly carbon-absorbing and dense MOF-functionalized nanofiber membrane in Example 1.

[0033] Figure 8 It is the pore size distribution curve of the strongly carbon-absorbing and dense MOF-functionalized nanofiber membrane in Example 1.

[0034] Figure 9 It is the scanning electron microscope image of the strongly carbon-absorbing and dense MOF-functionalized nanofiber membrane in Example 2.

[0035] Figure 10 It is the scanning electron microscope image of the strongly carbon-absorbing and dense MOF-functionalized nanofiber membrane in Example 3.

[0036] Figure 11 It is the scanning electron microscope image of the strongly carbon-absorbing and dense MOF-functionalized nanofiber membrane in Example 4. Detailed implementation manners

[0037] To make the objectives, technical solutions and advantages of the present invention clearer, the technical solutions of the present invention will be described in detail below. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other implementation manners obtained by those of ordinary skill in the art without creative efforts shall fall within the scope protected by the present invention. The present invention will be described in detail below with reference to the embodiments.

[0038] Such as Figure 1As shown in the figure, Embodiment 1 of the present invention provides a method for preparing a strongly carbon-absorbing dense MOF-functionalized nanofiber membrane by in-situ synthesis during spinning, comprising the following steps: Step S11, preparing a bimetallic spinning precursor solution: Dissolving polylactic acid, zinc acetate dihydrate, and cobalt acetate tetrahydrate in dichloromethane (the mass fraction of polylactic acid in the spinning precursor solution is 10%, the mass ratio of polylactic acid to zinc acetate dihydrate is 2:1, and the mass ratio of polylactic acid to cobalt acetate tetrahydrate is 2:1) to prepare a bimetallic spinning precursor solution; Step S12, preparing a metal salt-loaded nanofiber membrane: Subjecting the bimetallic spinning precursor solution obtained in Step S11 to high-voltage electrospinning (the working voltage is 30 kV, the receiving distance is 20 cm, the solution feeding rate is 1.5 mL / h, the nozzle diameter is 0.5 mm, the collector rotation speed is 2000 rpm, the temperature is 30°C, and the humidity is 30% RH) (the obtained nanofiber membrane has a thickness of 100 μm and a nanofiber diameter of 400 nm) to prepare a metal salt-loaded nanofiber membrane; Step S13, preparing a dense MOF-functionalized nanofiber membrane: In-situ synthesizing the metal salt-loaded nanofiber membrane obtained in Step S12 in a ligand solution composed of 2-methylimidazole (the total mass ratio of zinc acetate dihydrate and cobalt acetate tetrahydrate to 2-methylimidazole is 4:1) and ethanol at 25°C for 4 h to prepare a dense MOF-functionalized nanofiber membrane; Step S14, preparing a strongly carbon-absorbing dense MOF-functionalized nanofiber membrane: Subjecting the dense MOF-functionalized nanofiber membrane obtained in Step S13 to amination modification in a mixed solution of 3-aminopropyltrimethoxysilane and ethanol (the mass ratio of the nanofiber membrane to 3-aminopropyltrimethoxysilane and ethanol is 1:8:25) at 25°C for 12 h to prepare a strongly carbon-absorbing dense MOF-functionalized nanofiber membrane. The specific surface area of the obtained nanofiber membrane is 681 m 2 / g, and the average pore diameter is 0.69 nm.

[0039] As Figure 2 shown, the scanning electron microscope image of the strongly carbon-absorbing dense MOF-functionalized nanofiber membrane obtained in Embodiment 1 of the present invention shows that the surface of the polylactic acid nanofibers becomes rough, and the MOFs nanocrystals show a dense and uniform growth state on the surface of the polylactic acid nanofiber membrane, and the loading amount of the MOFs nanocrystals is 75 wt%.

[0040] As Figure 3 shown, the transmission electron microscope image of the strongly carbon-absorbing dense MOF-functionalized nanofiber membrane obtained in Embodiment 1 of the present invention confirms that the MOFs nanocrystals are uniformly distributed on the entire surface of the nanofibers.

[0041] As Figure 4 shown, the element mapping image of the strongly carbon-absorbing dense MOF-functionalized nanofiber membrane obtained in Embodiment 1 of the present invention shows that the two metal ion clusters on the surface of the nanofiber membrane are uniformly distributed, the cobalt content is about 53%, the zinc content is about 46%, and the large amount of metal element content provides sufficient nucleation sites for the MOFs nanocrystals.

[0042] AsFigure 5 As shown in the figure, the Fourier transform infrared spectroscopy (FTIR) spectrum of the strongly carbon-absorbing and dense MOF-functionalized nanofiber membrane obtained in Example 1 of the present invention shows new absorption peaks at 1590, 1485, 1145, 763, and 422 cm −1 . These peaks represent the stretching vibrations of C=N, N–H, C–N, and Zn–O / Co–O bonds, indicating the successful growth of ZIF-8, ZIF-67, and bimetallic Zn / Co-ZIF nanocrystals on the surface of the polylactic acid nanofiber membrane.

[0043] As Figure 6 shown in the figure, the powder X-ray diffraction pattern of the strongly carbon-absorbing and dense MOF-functionalized nanofiber membrane obtained in Example 1 of the present invention shows characteristic diffraction signal peaks originating from the (011), (002), (112), and (222) crystal planes.

[0044] As Figure 7 shown in the figure, the nitrogen adsorption-desorption isotherm curve of the strongly carbon-absorbing and dense MOF-functionalized nanofiber membrane obtained in Example 1 of the present invention shows a combination of type I and type III isotherms, indicating the presence of abundant micropores and macropore structures. The micropores originate from the MOF nanocrystals, and the macropores are attributed to the polylactic acid nanofiber membrane.

[0045] As Figure 8 shown in the figure, the pore size distribution curve of the strongly carbon-absorbing and dense MOF-functionalized nanofiber membrane obtained in Example 1 of the present invention shows that the nanofiber membrane has a hierarchical porous structure, and the main pore sizes are concentrated in the micropore and mesopore regions, which is beneficial to gas diffusion and adsorption.

[0046] Example 2 of the present invention provides a method for preparing a strong carbon-absorbing dense MOF-functionalized nanofiber membrane by in-situ synthesis during spinning, including the following steps: Step S21, preparing a bimetallic spinning precursor solution: Dissolve polylactic acid, zinc nitrate hexahydrate, and cobalt nitrate hexahydrate in N,N-dimethylformamide (the mass fraction of polylactic acid in the spinning precursor solution is 12%, the mass ratio of polylactic acid to zinc nitrate hexahydrate is 1:1, and the mass ratio of polylactic acid to cobalt nitrate hexahydrate is 1:1) to prepare a bimetallic spinning precursor solution; Step S22, preparing a nanofiber membrane loaded with metal salts: Pass the bimetallic spinning precursor solution obtained in Step S21 through wet solution spinning (the pore diameter of the spinneret is 0.1 - 0.5 mm, the spinneret pressure is 0.1 - 1 MPa, the injection speed is 1 - 10 mL / min, and the receiving distance is 10 - 30 cm) (the obtained nanofiber membrane has a thickness of 50 μm and a nanofiber diameter of 200 nm) to prepare a nanofiber membrane loaded with metal salts; Step S23, preparing a dense MOF-functionalized nanofiber membrane: In-situ synthesize the nanofiber membrane loaded with metal salts obtained in Step S22 in a ligand solution composed of 2-ethylimidazole (the total mass ratio of zinc nitrate hexahydrate and cobalt nitrate hexahydrate to 2-ethylimidazole is 2:1) and methanol at 10°C for 2 h to prepare a dense MOF-functionalized nanofiber membrane; Step S24, preparing a strong carbon-absorbing dense MOF-functionalized nanofiber membrane: Perform an amination modification reaction on the nanofiber membrane obtained by densifying MOF in Step S23 in a mixed solution of 3-aminopropyltriethoxysilane and methanol (the mass ratio of the nanofiber membrane to 3-aminopropyltriethoxysilane and methanol is 1:5:20) at 0°C for 6 h to prepare a strong carbon-absorbing dense MOF-functionalized nanofiber membrane. The specific surface area of the obtained nanofiber membrane is 633 m 2 / g, and the average pore diameter is 0.82 nm.

[0047] As Figure 9 shown, the scanning electron microscope image of the strong carbon-absorbing dense MOF-functionalized nanofiber membrane obtained in Example 2 of the present invention shows that the surface of the polylactic acid nanofibers becomes rough, and the MOFs nanocrystals show a dense and uniform growth state on the surface of the polylactic acid nanofiber membrane, and the loading amount of the MOFs nanocrystals is 72 wt%.

[0048] Example 3 of the present invention provides a method for preparing a strongly carbon-absorbing dense MOF-functionalized nanofiber membrane by in-situ synthesis during spinning, including the following steps: Step S31, preparing a bimetallic spinning precursor solution: Dissolve polylactic acid, zinc sulfate heptahydrate, and cobalt sulfate heptahydrate in chloroform (the mass fraction of polylactic acid in the spinning precursor solution is 14%, the mass ratio of polylactic acid to zinc sulfate heptahydrate is 3:1, and the mass ratio of polylactic acid to cobalt sulfate heptahydrate is 3:2) to prepare a bimetallic spinning precursor solution; Step S32, preparing a metal salt-loaded nanofiber membrane: Pass the bimetallic spinning solution obtained in Step S31 through rotary centrifugal spinning (the rotation speed is 10,000 rpm, the rotation radius is 3 cm, the nozzle diameter is 0.3 mm, the receiving distance is 30 cm, the solution flow rate is 2 mL / h, and the ambient temperature is 40°C) (the obtained nanofiber membrane has a thickness of 150 μm and a nanofiber diameter of 600 nm) to prepare a metal salt-loaded nanofiber membrane; Step S33, preparing a dense MOF-functionalized nanofiber membrane: In-situ synthesize the metal salt-loaded nanofiber membrane obtained in Step S32 in a ligand solution composed of 2-aminoimidazole (the total mass ratio of zinc sulfate heptahydrate and cobalt sulfate heptahydrate to 2-aminoimidazole is 2:3) and water at 40°C for 12 h to prepare a dense MOF-functionalized nanofiber membrane; Step S34, preparing a strongly carbon-absorbing dense MOF-functionalized nanofiber membrane: Perform amino-functionalization modification on the dense MOF-functionalized nanofiber membrane obtained in Step S33 in a mixed solution of N-methyl-3-aminopropyltrimethoxysilane and water (the mass ratio of the nanofiber membrane to N-methyl-3-aminopropyltrimethoxysilane and water is 1:10:30) at 40°C for 24 h to prepare a strongly carbon-absorbing dense MOF-functionalized nanofiber membrane. The specific surface area of the obtained nanofiber membrane is 579 m 2 / g, and the average pore diameter is 1.01 nm.

[0049] As Figure 10 shown, the scanning electron microscope image of the strongly carbon-absorbing dense MOF-functionalized nanofiber membrane obtained in Example 3 of the present invention shows that the surface of the polylactic acid nanofibers becomes rough, and the MOF nanocrystals show a dense and uniform growth state on the surface of the polylactic acid nanofiber membrane, and the loading amount of the MOF nanocrystals is 68 wt%.

[0050] Example 4 of the present invention provides a method for preparing a strongly carbon-absorbing dense MOF-functionalized nanofiber membrane by in-situ synthesis during spinning, including the following steps: Step S41, preparing a bimetallic spinning precursor solution: dissolving polylactic acid, zinc chloride, and cobalt chloride hexahydrate in acetone (the mass fraction of polylactic acid in the spinning precursor solution is 16%, the mass ratio of polylactic acid to zinc chloride is 5:2, and the mass ratio of polylactic acid to cobalt chloride hexahydrate is 5:1) to prepare a bimetallic spinning precursor solution; Step S42, preparing a metal salt-loaded nanofiber membrane: passing the bimetallic spinning precursor solution obtained in Step S41 through rotary centrifugal spinning (the rotation speed is 10,000 rpm, the rotation radius is 3 cm, the nozzle diameter is 0.3 mm, the receiving distance is 30 cm, the solution flow rate is 2 mL / h, and the ambient temperature is 40°C) (the obtained nanofiber membrane has a thickness of 190 μm and a nanofiber diameter of 700 nm) to prepare a metal salt-loaded nanofiber membrane; Step S43, preparing a dense MOF-functionalized nanofiber membrane: in-situ synthesizing the metal salt-loaded nanofiber membrane obtained in Step S42 in a ligand solution composed of 2-methylbenzimidazole (the total mass ratio of zinc sulfate heptahydrate and cobalt sulfate heptahydrate to 2-methylbenzimidazole is 2:5) and acetone at 50°C for 24 h to prepare a dense MOF-functionalized nanofiber membrane; Step S44, preparing a strongly carbon-absorbing dense MOF-functionalized nanofiber membrane: subjecting the dense MOF-functionalized nanofiber membrane obtained in Step S43 to amino modification in a mixed solution of 3-aminopropyltrimethoxysilane and N,N-dimethylformamide (the mass ratio of the nanofiber membrane to 3-aminopropyltrimethoxysilane and N,N-dimethylformamide is 1:15:40) at 50°C for 48 h to prepare a strongly carbon-absorbing dense MOF-functionalized nanofiber membrane. The specific surface area of the obtained nanofiber membrane is 527 m 2 / g, and the average pore diameter is 1.22 nm.

[0051] As Figure 11 shown, the scanning electron microscope image of the strongly carbon-absorbing dense MOF-functionalized nanofiber membrane obtained in Example 4 of the present invention shows that the surface of the polylactic acid nanofibers becomes rough, and the MOFs nanocrystals show a dense and uniform growth state on the surface of the polylactic acid nanofiber membrane, and the loading amount of the MOFs nanocrystals is 65 wt%.

[0052] Comparative Example 1 of the present invention provides a method for preparing a strong carbon-absorbing dense MOF-functionalized nanofiber membrane, which basically adopts the method of Example 1 to prepare a strong carbon-absorbing dense MOF-functionalized nanofiber membrane. The difference is that in this example, only a zinc source and an organic ligand are used to react to prepare a strong carbon-absorbing dense MOF-functionalized nanofiber membrane. Poly(lactic acid) and zinc acetate dihydrate are dissolved in dichloromethane (the mass fraction of poly(lactic acid) in the spinning solution is 10%, and the mass ratio of poly(lactic acid) to zinc acetate dihydrate is 2:1) to prepare a metal spinning precursor solution; the obtained metal spinning precursor solution is subjected to high-voltage electrospinning (the working voltage is 30 kV, the receiving distance is 20 cm, the solution feeding rate is 1.5 mL / h, the nozzle diameter is 0.5 mm, the collector rotation speed is 2000 rpm, the temperature is 30 °C, and the humidity is 30% RH) (the obtained nanofiber membrane has a thickness of 100 μm and a nanofiber diameter of 400 nm) to prepare a metal salt-loaded nanofiber membrane; the obtained metal salt-loaded nanofiber membrane is in-situ synthesized in a ligand solution composed of 2-methylimidazole (the mass ratio of zinc acetate dihydrate to 2-methylimidazole is 2:1) and ethanol at 25 °C for 4 h to prepare a dense MOF-functionalized nanofiber membrane; the obtained dense MOF-functionalized nanofiber membrane is subjected to amino modification in a mixed solution of 3-aminopropyltrimethoxysilane and ethanol (the mass ratio of the nanofiber membrane to 3-aminopropyltrimethoxysilane and ethanol is 1:8:25) at 25 °C for 12 h to prepare a strong carbon-absorbing dense MOF-functionalized nanofiber membrane.

[0053] Comparative Example 2 of the present invention provides a method for preparing a strong carbon-absorbing dense MOF-functionalized nanofiber membrane, which basically adopts the method of Example 2 to prepare a strong carbon-absorbing dense MOF-functionalized nanofiber membrane. The difference is that in this example, only a cobalt source and an organic ligand are used to react to prepare a strong carbon-absorbing dense MOF-functionalized nanofiber membrane. Poly(lactic acid) and cobalt nitrate hexahydrate are dissolved in N,N-dimethylformamide (the mass fraction of poly(lactic acid) in the spinning solution is 12%, and the mass ratio of poly(lactic acid) to cobalt acetate tetrahydrate is 1:1) to prepare a metal spinning precursor solution; the obtained metal spinning precursor solution is subjected to wet solution spinning (the spinneret pore diameter is 0.1 - 0.5 mm, the spinneret pressure is 0.1 - 1 MPa, the injection speed is 1 - 10 mL / min, and the receiving distance is 10 - 30 cm) to prepare a metal salt-loaded nanofiber membrane; the obtained metal salt-loaded nanofiber membrane is in-situ synthesized in a ligand solution composed of 2-ethylimidazole (the mass ratio of cobalt nitrate hexahydrate to 2-ethylimidazole is 1:1) and methanol at 10 °C for 2 h to prepare a dense MOF-functionalized nanofiber membrane; the obtained dense MOF-functionalized nanofiber membrane is subjected to amino modification in a mixed solution of 3-aminopropyltriethoxysilane and methanol (the mass ratio of the nanofiber membrane to 3-aminopropyltriethoxysilane and methanol is 1:5:20) at 0 °C for 6 h to prepare a strong carbon-absorbing dense MOF-functionalized nanofiber membrane.

[0054] Comparative Example 3 of the present invention provides a method for preparing a strong carbon-absorbing and dense MOF-functionalized nanofiber membrane, and basically uses the method of Example 3 to prepare a strong carbon-absorbing and dense MOF-functionalized nanofiber membrane. The difference is that in this example, a silane reagent is not used for amino modification to prepare a strong carbon-absorbing and dense MOF-functionalized nanofiber membrane. Dissolve polylactic acid, zinc sulfate heptahydrate and cobalt sulfate heptahydrate in chloroform (the mass fraction of polylactic acid in the spinning solution is 14%, the mass ratio of polylactic acid to zinc sulfate heptahydrate is 3:1, the mass ratio of polylactic acid to cobalt sulfate heptahydrate is 3:2, and the mass ratio of zinc sulfate heptahydrate to cobalt sulfate heptahydrate is 1:2) to prepare a bimetallic spinning precursor solution; spin the obtained bimetallic spinning precursor solution by rotary centrifugal spinning (the rotation speed is 10,000 rpm, the rotation radius is 3 cm, the nozzle diameter is 0.3 mm, the receiving distance is 30 cm, the solution flow rate is 2 mL / h, and the ambient temperature is 40°C) to prepare a metal salt-loaded nanofiber membrane; in situ synthesize the obtained metal salt-loaded nanofiber membrane in a ligand solution composed of 2-aminoimidazole (the mass ratio of zinc sulfate heptahydrate, cobalt sulfate heptahydrate and 2-aminoimidazole is 1:1:3) and water at 40°C for 12 h to prepare a strong carbon-absorbing and dense MOF-functionalized nanofiber membrane.

[0055] The structure characterization and performance tests are as follows.

[0056] Scanning electron microscope observation: Observe the microstructure of the strong carbon-absorbing and dense MOF-functionalized nanofiber membrane through a field emission scanning electron microscope (model JSM-7900F, JEOL, Japan) ( Figure 2 , Figure 9 , Figure 10 , Figure 11 ).

[0057] Transmission electron microscope observation: Observe the microstructure of the strong carbon-absorbing and dense MOF-functionalized nanofiber membrane through a transmission electron microscope (model TECNI G2 TF20, FEI) ( Figure 3 ).

[0058] Surface element distribution test: Use an energy dispersive X-ray spectrometer (model Vario EL, JEOL, Japan) to record the surface element distribution of the strong carbon-absorbing and dense MOF-functionalized nanofiber membrane ( Figure 4 ).

[0059] Functional group structure test: Use an infrared spectrometer (model VERTEX 70, Bruker, USA) to record the functional groups of the strong carbon-absorbing and dense MOF-functionalized nanofiber membrane ( Figure 5 ).

[0060] Crystal structure test: Use an X-ray spectrometer (model D / Max-2400, Rigaku Corporation, Japan) to record the crystal structure of the strong carbon-absorbing and dense MOF-functionalized nanofiber membrane ( Figure 6 ).

[0061] Specific surface area measurement: The nitrogen adsorption - desorption isotherm and pore size distribution curve of the strongly carbon - adsorbing dense MOF - modified nanofiber membrane were measured at 77 K using a gas sorption analyzer (ASAP 2060, Micromeritics, USA). Figure 7 , Figure 8 ).

[0062] Gas adsorption performance measurement: A gas sorption analyzer (ASAP 2020, Micromeritics, USA) was used to adsorb CO2, CH4, and N2 on the strongly carbon - adsorbing dense MOF - modified nanofiber membrane. High - purity gases CO2 (99.999%), CH4 (99.999%), and N2 (99.999%) were used for adsorption measurement, while helium (99.999%) was used to measure the free space. Isothermal adsorption was carried out at 273 K (ice - water bath).

[0063] Experimental results: As shown in Figure 2 , Figure 9 , Figure 10 and Figure 11 , the synthesized strongly carbon - adsorbing dense MOF - modified nanofiber membrane exhibited a three - dimensional structure of fine nanofibers with random orientation. The fiber surface was rough, showing a core - shell structure formed by the in - situ self - assembled growth of MOFs nanocrystals at room temperature. Notably, the diameter of the nanofibers increased significantly, and the uniform and dense growth of MOFs nanocrystals endued the nanofiber membrane with a high metal framework loading.

[0064] As shown in Figure 3 , the synthesized strongly carbon - adsorbing dense MOF - modified nanofiber membrane showed a uniform distribution of Zn / Co - MOFs nanocrystals on the entire nanofiber surface, presenting a core - shell structure with polylactic acid nanofibers as the core and Zn / Co - MOFs nanocrystals as the shell layer.

[0065] As shown in Figure 4 , the synthesized strongly carbon - adsorbing dense MOF - modified nanofiber membrane showed a uniform distribution of two metal ion clusters on the nanofiber membrane surface. The cobalt content was approximately 53%, and the zinc content was approximately 46%. The large amount of metal elements provided sufficient nucleation sites for the MOFs crystals.

[0066] As shown in Figure 5 , the synthesized strongly carbon - adsorbing dense MOF - modified nanofiber membrane showed new absorption peaks at 1590, 1485, 1145, 763, and 422 cm −1 , indicating the successful growth of ZIF - 8, ZIF - 67, and bimetallic Zn / Co - ZIF crystals on the surface of the polylactic acid nanofiber membrane, representing the stretching vibrations of C=N, N–H, C–N, and Zn–O / Co–O bonds.

[0067] As shown in Figure 6As shown, characteristic diffraction signal peaks originating from the (011), (002), (112), and (222) crystal planes were observed in the powder X-ray diffraction pattern of the obtained strongly carbon-absorbing and dense MOF-functionalized nanofiber membrane.

[0068] As Figure 7 shown, for the nitrogen adsorption-desorption isotherm curve of the obtained strongly carbon-absorbing and dense MOF-functionalized nanofiber membrane, the fiber membrane exhibited a combination of type I and type III isotherms, indicating the presence of abundant micropores and macropores. The micropores originated from MOF nanocrystals, and the macropores were attributed to the polylactic acid nanofiber membrane.

[0069] As Figure 8 shown, for the pore size distribution curve of the obtained strongly carbon-absorbing and dense MOF-functionalized nanofiber membrane, it indicated that the nanofiber membrane had a hierarchical porous structure, and the main pore sizes were concentrated in the micropore and mesopore regions, which was beneficial to gas diffusion and adsorption.

[0070] Table 1 compares the specific surface area, average pore size, metal framework loading, CO2 adsorption capacity, and CO2 / N2 and CO2 / CH4 separation selectivity results of the strongly carbon-absorbing and dense MOF-functionalized nanofiber membranes obtained in the examples and comparative examples.

[0071] Table 1

[0072] Examples 1 to 4 had a relatively high specific surface area (527 m 2 / g to 681 m 2 / g) and a relatively small pore size (0.69 nm to 1.22 nm). This was because highly porous bimetallic MOF nanocrystals were in-situ synthesized on the surface of polylactic acid fibers through electrospinning induction, endowing the nanofiber membrane with a high specific surface area and abundant microporous structure. The specific surface area of Comparative Example 1 was only 43 m 2 / g, and the average pore size was 20.4 nm. This was because there were no pre-set metal reaction binding sites inside the polylactic acid nanofiber membrane, and MOF nanocrystals could not grow to form a porous structure.

[0073] The CO2 adsorption capacity, separation selectivity of the strongly CO2 - adsorbing and dense MOF - modified nanofiber membrane are closely related to specific surface area, pore size, dense MOF modification and amino modification. For Examples 1 - 4 with large specific surface area, small pore size, dense MOF modification and amino - modified adsorption sites, the CO2 adsorption capacity is above 3.6 mmol / g, the CO2 / N2 separation selectivity is above 132, and the CO2 / CH4 separation selectivity is above 32, showing good CO2 adsorption and separation selectivity. Among them, Example 1 with the highest specific surface area, the smallest pore size, dense MOF modification and amino modification performs the best in gas adsorption and separation tests, with a CO2 adsorption capacity of 4.7 mmol / g, a CO2 / N2 separation selectivity of 132, and a CO2 / CH4 separation selectivity of 61, far higher than Comparative Examples 1 - 3 with low specific surface area, large pore size, low dense MOF modification and no amino modification (CO2 adsorption capacity ≤ 2.3 mmol / g, CO2 / N2 separation selectivity ≤ 47, CO2 / CH4 separation selectivity ≤ 17).

[0074] The present invention provides a method for in - situ synthesis of a strongly CO2 - adsorbing and dense MOF - modified nanofiber membrane by spinning induction, as well as its preparation method and application. There are many specific methods and ways to implement this technical solution. The above - mentioned is only the preferred embodiment of the present invention. It should be noted that for those of ordinary skill in the art, without departing from the principle of the present invention, several improvements and refinements can be made, and these improvements and refinements should also be regarded as the protection scope of the present invention. Each component not clearly defined in this embodiment can be realized by existing technologies.

Claims

1. A method for preparing a spinning-induced in-situ synthesis of a dense MOF nanofiber membrane with strong carbon absorption, characterized in that: The following steps are involved: Step S1, dissolving polylactic acid, a zinc source and a cobalt source in a solvent A to prepare a bimetallic spinning precursor solution; Step S2, preparing a metal salt-loaded nanofiber membrane by spinning the bimetallic spinning precursor solution obtained in step S1; Step S3, in situ synthesizing the metal salt-loaded nanofiber membrane obtained in step S2 in a ligand solution consisting of an organic ligand and a solvent B to prepare a dense MOF nanofiber membrane; Step S4, the dense MOF nanofiber membrane obtained in step S3 is subjected to amino modification in a mixed solution consisting of a silane reagent and a solvent C to prepare a spinning-induced in-situ synthesized strong carbon-absorbing dense MOF nanofiber membrane.

2. The method for preparing a spinning-induced in-situ synthesized strong carbon-absorbing dense MOF nanofiber membrane according to claim 1, characterized in that: In the step S1, the zinc source is one or more of zinc acetate dihydrate, zinc nitrate hexahydrate, zinc sulfate heptahydrate, zinc chloride, zinc perchlorate, zinc fluoride, zinc formate, and zinc citrate; the cobalt source is one or more of cobalt nitrate hexahydrate, cobalt acetate tetrahydrate, cobalt sulfate heptahydrate, cobalt chloride hexahydrate, cobalt carbonate, cobalt oxalate dihydrate, cobalt hydroxide, cobalt oxide, cobalt acetylacetonate, and cobalt perchlorate hexahydrate; and the solvent A in the step S1 is one or more of dichloromethane, N,N-dimethylformamide, chloroform, methanol, ethanol, acetone, tetrahydrofuran, N,N-dimethylacetamide, hexafluoroisopropanol, dioxane, toluene, and dimethyl sulfoxide.

3. The method for preparing a spinning-induced in-situ synthesized strong carbon-absorbing dense MOF nanofiber membrane according to claim 1, characterized in that: In the step S1, the mass ratio of polylactic acid to zinc source is 10:1-1:10, the mass ratio of polylactic acid to cobalt source is 10:1-1:10, and the mass fraction of polylactic acid in the bimetallic spinning precursor solution obtained in step S1 is 5%-25%.

4. The method for preparing a spinning-induced in-situ synthesized strong carbon-absorbing dense MOF nanofiber membrane according to claim 1, characterized in that: The spinning process in step S2 is one or more of high-voltage electrospinning, wet solution spinning, dry solution spinning, rotary centrifugal spinning, high-speed airflow spinning, microfluidic spinning, emulsion spinning, reaction spinning, gel spinning, and liquid crystal spinning processes. The metal salt-loaded nanofiber membrane obtained in step S2 has a thickness of 50 to 200 μm and a nanofiber diameter of 200 to 900 nm.

5. The method for preparing a spinning-induced in-situ synthesized strong carbon-absorbing dense MOF nanofiber membrane according to claim 1, characterized in that: In the step S3, the organic ligand is one or more of 2-methylimidazole, 4-methylimidazole, 2-ethylimidazole, 2-aminoimidazole, 2-methylbenzimidazole, 1-vinylimidazole, 2-ethylbenzimidazole, 1-phenylimidazole, and 2-aminobenzimidazole; and in the step S3, the solvent B is one or more of water, methanol, ethanol, N,N-dimethylformamide, N,N-dimethylacetamide, toluene, chloroform, acetone, tetrahydrofuran, and ionic liquid.

6. The method for preparing a spinning-induced in-situ synthesized strong carbon-absorbing dense MOF nanofiber membrane according to claim 1, characterized in that: The mass ratio of the organic ligand in step S3 to the total zinc source and cobalt source in the metal salt-loaded nanofiber membrane obtained in step S2 is 10:1-1:10, and the in-situ synthesis conditions are as follows: temperature is 0-50°C and time is 0.5-24 h.

7. The method for preparing a spinning-induced in-situ synthesized strong carbon-absorbing dense MOF nanofiber membrane according to claim 1, characterized in that: In the step S4, the silane reagent is one or more of 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-aminopropylmethyldimethoxysilane, N-methyl-3-aminopropyltrimethoxysilane, 3-aminopropyltrimethoxysilane, and 4-aminophenyltrimethoxysilane. In the step S4, the solvent C is one or more of methanol, ethanol, N,N-dimethylformamide, N,N-dimethylacetamide, water, toluene, chloroform, dimethyl sulfoxide, and N-methyl-2-pyrrolidone.

8. The method for preparing a spinning-induced in-situ synthesized strong carbon-absorbing dense MOF nanofiber membrane according to claim 1, characterized in that: The mass ratio of the silane reagent in step S4 to the solvent C in step S4 and the dense MOF nanofiber membrane obtained in step S3 is 5-15:20-40:1, and the conditions for the amino modification in step S4 are temperature of 0-60°C and time of 1-48h.

9. A strong carbon-absorbing dense MOF nanofiber membrane prepared by the method for preparing a spinning-induced in-situ synthesized strong carbon-absorbing dense MOF nanofiber membrane according to any one of claims 1 to 8, characterized in that: The specific surface area of ​​the nanofiber membrane is 527m 2 / g~681 m 2 / g, pore size is 0.69 nm~1.22 nm, and MOF loading is 65~75 wt%.

10. Application of the highly carbon-absorbing and dense MOF nanofiber membrane according to claim 9 in carbon capture in industrial terminal exhaust gas, energy production process, transportation, agriculture and ecology, and biomedicine and semiconductor precision manufacturing industries.

Citation Information

Cited By

  • Metal organic framework fiber method, application, and filter thereof

    TWI924581B